Experimental investigation and modelling of flexural properties of carbon textile reinforced concrete. (30th November 2020) - Halvaei, Mana; Jamshidi, Masoud; Latifi, Masoud; Ejtemaei, Mojtaba
Highlights: Carbon textile reinforced fine aggregate concrete were evaluated for flexural properties. The flexural properties were evaluated using experimental and ANN modeling. The carbon textile were woven in lab. with different mesh sizes and volume fractions. The correlation between mesh size and volume fraction of textile were studied. Abstract: In this study, carbon woven textiles with mesh sizes from 0 to 20 mm at both constant and different volume percentages were woven and applied to fine aggregate concretes. Four-point bending test and scanning electron microscopy were carried out on the specimens to investigate the flexural behavior and microstructure of the samples, respectively. The flexural load and toughness of the samples were increased more than 380% and 820%, respectively, by a decrease in the textile mesh size from 20 to 2 mm. This was attributed to an increase in the textile volume percentages. However, the sample contained textile with the mesh size of zero showed weaker performance due to decrease in the penetration of the cement matrix into the textile structure. By using textiles with different mesh sizes but the same volume contents, it was found that the mesh size of the textile, in contrast to volume content, is not dominant factor on flexural behavior of the TRCs. Finally, artificial neural network (ANN) was used to model flexural strength of the samples. It was shown that ANN is an effecting technique for predicting the flexural strength of the carbon textile reinforced concrete samples.